2003
DOI: 10.1038/sj.sc.3101404
|View full text |Cite
|
Sign up to set email alerts
|

Complex regional pain syndrome – diagnostic, mechanisms, CNS involvement and therapy

Abstract: Complex regional pain syndromes (CRPS, formerly re¯ex sympathetic dystrophy and causalgia) are neuropathic pain conditions of one extremity developing inadequately after a trauma. The initiating trauma aects primarily the extremity, but can also be a central lesion (e.g., spinal cord injury, stroke). CRPS is clinically characterized by sensory, autonomic and motor disturbances. Pathophysiologically there is evidence for functional changes within the central nervous system and for involvement of peripheral in¯a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
105
0
9

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(114 citation statements)
references
References 144 publications
0
105
0
9
Order By: Relevance
“…Moreover, limb position sense is integral to motor performance yet motor dysfunction is well recognised in CRPS [4,13,14,22,24,38,45,46,47,48]. Brainimaging evidence of altered neural activity in motor cortices has also been found [29].…”
Section: Introduction "If the Pain Is Very Intense Even If I Am Toucmentioning
confidence: 93%
“…Moreover, limb position sense is integral to motor performance yet motor dysfunction is well recognised in CRPS [4,13,14,22,24,38,45,46,47,48]. Brainimaging evidence of altered neural activity in motor cortices has also been found [29].…”
Section: Introduction "If the Pain Is Very Intense Even If I Am Toucmentioning
confidence: 93%
“…A study demonstrated that peripheral traumatic injury of the shoulder joint capsules led to painful extremities after stroke [9]. Some authors claimed that peripheral lesions might initiate a self-perpetuating vicious cycle of pain followed by the full picture of RSDS [10]. We assumed that in stroke patients with extremity OB, like our case, appears to be at a significantly higher risk of developing RSDS.…”
Section: Discussionmentioning
confidence: 70%
“…8,9 Gellman et al 10 identified a 10% incidence of CRPS type I in their series of 60 patients with tetraplegia. Cremer et al 2 showed an association between CRPS type I and traumatic myelopathy in five In the literature published so far, CRPS type I in tetraplegic patients has mostly occurred in the upper extremities, with lower extremity involvement mentioned in only one report.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of CRPS type I should be immediate and, most importantly, should be directed toward restoration of full function of the extremity. 9 Multiple treatment modalities in CRPS type I have been described. In our patient, we used TENS together with Amitriptyline and Calcitonin in pain control.…”
Section: Discussionmentioning
confidence: 99%